The Study of Performance of Provincial Governments: Does Frequent Transfer of Officials Matter? - Kharel, Tara Prasad; Adhikari, Rajendra (Prashasan: The Nepalese Journal of Public Administration, 2023)
Nepal is federal country with three levels of governments, viz. federal, province and local. Among these, province government is new structure and its performance is important for the stability of province and the federal system. The performance of province is mainly determined by the frequency of transfer of top level bureaucrats and the availability of the staffs in province ministry. This study establishes the relation between frequent transfer of top level bureaucrats, availability of staffs and the performance of province government further digging out other factors affecting the performance of province government. The purpose of the study is to examine data from secondary sources, focus groups, field observations, interviews with key informants, and other sources that includes both quantitative and qualitative data. The study established the relation between performances of province government with frequent transfer of top level bureaucrats of province ministries of Lumbini Province. There has been effect of such frequent transfer of the top level bureaucrats in the performance of Lumbini Province government to the large extent in planning, implementation, resource management, risk management, liability management, accountable management, effectiveness of office, coordination among other staffs and offices, and policy making. But the impact on daily office operation has been found very low. Federal and province governments are suggested to reduce the frequent transfer of top level bureaucrats and manage the full staffing condition of province ministries.